Influences of Neuromuscular Facilitation in the hamstrings and quadriceps muscles of Parkinsonian elderly. - Carvalho, Emilton Lima de; Cruz, Karoline Lisandra Teixeira; Queiroz, Ilkenison Pinheiro; Silva, Flávio; Maciel, Thiago dos Santos; Arêas, Fernando Zanela da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Parkinson’s disease (PD) is a type of neurodegenerative disease that affects between 4.1 and 4.6 million people in the 10 most populous nations of the world, worldwide approximately 7 million people are affected by PD, both affected with age or more than 50 years, this problem affects the independent subjects of sex and its most important pathological finding is the injury of the black substance, which is located in the basal ganglia Objective: to evaluate and quantify the effects of PNF technique on individuals Parkinsonian residents in Coari-AM city, being evaluated areas of strength and flexibility of the hamstrings and quadriceps muscles. Methods: five elderly diagnosed with PD and mean age 82.5 ± 10.33 were performed, anamnesis, screening and evaluation of the strength and flexibility of the quadriceps and hamstring muscles bilaterally. The treatment protocol consisted of 10 sessions, often at least 3 times a week and estimated treatment time 50 minutes. Results: It was observed that all the muscles tested positive at the beginning of treatment, for flexibility and power of them, however, after the application of any treatment, the quadriceps muscles did not show statistically significant improvement since the hamstring muscles presented significant improvements in both strength and flexibility, when analyzed belatedly. The results were adopted with significance values p <0.05. Conclusion: The PNF technique was positive for the immediate gains of flexibility and strength, however, after 10 sessions program, the results showed little variation, there were no significant differences in the strength of the quadriceps after the treatment program.